Identification and Classsification Cyber Bullying among University's Students - Paul Joae Brett Nito; Malisa Ariani; Onieqie Ayu Dhea Manto; Dewi Wulandari (Universitas Muhammadiyah Semarang, 2022)
The development of technology not only has a positive impact but also has a negative impact. One of them is the shift in bullying trends, from traditional bullying to cyberbullying. Based on a report, as many as 210.3 million internet users aged 13-17 years ranked third in using social media. Cyberbullying victims in Indonesia reach 41-50% and 80% of teenagers become victims of cyberbullying. This study aims to determine the incidence of cyberbullying in students. Using an analytical survey research method with a cross-sectional survey design. Data collection through Cyberbullying and Online Aggression Survey questionnaires and data processing is presented in the form of a frequency distribution. The results showed that 125 respondents (75%) who experienced cyberbullying with types of cyberbullying included flaming 32,14%; exclusion 62,75%; harassment 47,44%; flooding 50%; masquerade log in 42,34%; trolling 25,52%; denigration 19,89%; outing 25%; dan sexual harassment 15,3%. The incidence of cyberbullying in adolescents is still high and all types of cyberbullying have been experienced by adolescents.